Numerical simulation of spouting of cylindroid particles in a spouted bed. (13th August 2013) - Ren, Bing; Zhong, Wenqi; Jiang, Xiaofeng; Jin, Baosheng; Yuan, Zhulin
Abstract The hydrodynamic behaviours of cylindroid particles in a spouted bed are studied by three‐dimensionally coupled computational fluid dynamic (CFD) and discrete element method (DEM) model. The cylindroid particles are constructed by multi‐sphere method. The drag coefficient model for non‐spherical particles is employed which shows higher accuracy by comparing the calculated flow pattern and pressure drop distribution data with the experimental measurements and the predicted results with the traditional drag coefficient model for spherical particles. Peak pressure drop, flow pattern, spout diameter and geometry of the fountain are discussed in detail.